DEPRESSION AND ANXIETY AMONG PATIENTS SEEKING RHINOPLASTY - Khan, Sikandar Ali; Ali, Ghazanfar; Raza, Maqbool; Tariq, Muhammad; Adeel, Imran; Butt, Ahsan Masood (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the presence and relation of depression and anxiety among patients seeking rhinoplasty Study Design: A cross-sectional study. Place and Duration of Study: Departments of Psychiatry, department of Plastic Surgery and ENT, Combined Military Hospital Multan, from Jan 2019 to Mar 2020. Methodology: A total of 102 patients were recruited that reported to Plastic surgery and ENT unit. Patients were divided equally in two groups of 51 each. One group included patients seeking rhinoplasty while other group included those patients that reported in Plastic surgery and ENT unit for reasons other than rhinoplasty. Symptom were assessed using Beck Depressive Inventory for depression and Beck Anxiety Inventory for anxiety. Results: A total of 102 participants were included in the study, of these 51 were patients seeking rhinoplasty and 51 were controls. Significant correlation exist between anxiety and depression (p<0.00). Conclusion: There is a very high frequency of anxiety and depression among patients seeking Rhinoplasty along with significant positive correlation.